“The poor man’s son” and Adam Smith’s theory of beauty - Rathbone, Mark (Koers (Potchefstroom, South Africa), 2025)
The article’s novelty is its focus on the role of Smith’s theory of beauty and its implications for utility, systems, and morality in the narrative of “The Poor Man’s Son”. From his enlightenment worldview, the narrative contains Smith’s criticism of the misguided or reductionist view of the beauty of utility and affirmation of harmonious systems. Adam Smith’s narrative of “The Poor Man’s Son” in his book, The theory of moral sentiments [1759], has received significant attention from scholars. Three modes of interpretation can be distinguished. The first group follow a mode of interpretation from the world of the text, which is literal and regards the narrative as Smith’s support of beneficence. The narrative is perceived as Smith’s criticism of commerce and consumerism in pursuing happiness. The second group, reading from the world behind the text, pay more attention to historical and material aspects and argue that the narrative warns against misplaced ambition and affirms the virtue of commerce. The third group, reading from the world in front of the text, focus on the reception of the text, and the emphasis shifts to the tension between beneficence and commercial prowess in Smith’s work. The problem with all three interpretations is that the interrelated nature of beauty, utility, and commerce has not been explored. Consequently, an analysis of the narrative from Smith’s theory of beauty underscores that the poor man’s son’s anguish resulted from a lack of appreciation of the beauty of the economic system and not solely the pleasure of consumption. This unlocks the connection between beauty, utility, and commerce, affirming the common good and societal harmony of systems when artefacts function correctly.